Motivation Role in Improving Work Effectiveness - Yeti Kuswati (Budapest International Research and Critics University, 2019)
In an effort to realize the vision of the Regional Technical Implementation Unit (UPTD) of Irrigation Network at Talaga, Majalengka, which is